Why is Sharikov dead? The fate of "the Soviet Frankenstein" in Bulgakov's A Dog's Heart. Issue 1 (2nd January 2019) - Dame, Natalia
ABSTRACT: Many critics have identified Mary Shelley's novel Frankenstein, or the Modern Prometheus as one of the literary predecessors of Mikhail Bulgakov's novella A Dog's Heart . However, a brief comparison of these two works has not yet gone beyond establishing their basic thematic and structural similarities; the roots of these similarities lie in the Promethean myth and in the conventions of the science-fiction genre. This article investigates the changing relationship between Shelley's and Bulgakov's creators and creations through the prism of class struggle. In particular, the author examines how and why Bulgakov justifies what Shelley does not – the destruction of the creature by his creator. Having contextualized both works in their time and place, the study discusses Bulgakov's strategy for modifying Shelley's portrayal of class conflict in the Soviet setting. The first two parts of the discussion compare the two experimental beings in terms of their identity and behaviour and the two scientists in terms of their responsibility and accountability. The last part shows how Bulgakov's use of an animal character – the dog Sharik – not only motivates Preobrazhenskii's victory over Sharikov, but also highlights this victory's moral incertitude by revealing the mechanisms of a narrative that validates class and species violence.